2011
DOI: 10.1037/a0020712
|View full text |Cite
|
Sign up to set email alerts
|

Accent, perpetual foreigner stereotype, and perceived discrimination as indirect links between English proficiency and depressive symptoms in Chinese American adolescents.

Abstract: The current study uses Garcia Coll et al.'s (1996) developmental competence model of ethnic minority children and Kim's (1999) Racial Triangulation Theory as frameworks for investigating the mechanisms whereby early adolescent English proficiency relates to perceived discriminatory experiences and adolescent depressive symptoms. Data from 444 adolescents (239 girls and 205 boys, with a mean age of 13.0 for Wave 1 and 17.0 for Wave 2) and their parents living in major metropolitan areas of Northern California w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
122
2
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(138 citation statements)
references
References 74 publications
6
122
2
8
Order By: Relevance
“…Indeed, Latino and Asian American adolescents may face differential treatment that is distinct from those experienced by African Americans, such as discrimination from being stereotyped as foreigners. For instance, a longitudinal study of Chinese middle school students found that self-reported English proficiency in middle school was associated with perceptions of being stereotyped as foreigners in high school, which in turn was associated with discrimination (Kim et al 2011). In addition, both Latino and Asian Americans likely come from disadvantaged backgrounds in terms of lower education, use of public assistance, and a likelihood of living in poverty, which also may be grounds for differential treatment (Hwa-Froelich and Westby 2003).…”
Section: Latino and Asian American Adolescentsmentioning
confidence: 98%
“…Indeed, Latino and Asian American adolescents may face differential treatment that is distinct from those experienced by African Americans, such as discrimination from being stereotyped as foreigners. For instance, a longitudinal study of Chinese middle school students found that self-reported English proficiency in middle school was associated with perceptions of being stereotyped as foreigners in high school, which in turn was associated with discrimination (Kim et al 2011). In addition, both Latino and Asian Americans likely come from disadvantaged backgrounds in terms of lower education, use of public assistance, and a likelihood of living in poverty, which also may be grounds for differential treatment (Hwa-Froelich and Westby 2003).…”
Section: Latino and Asian American Adolescentsmentioning
confidence: 98%
“…These consequences are far from transitory; longitudinal analyses have shown that most, if not all, of these behaviors become increasingly linked with perceived discrimination over time (Benner & Kim, 2009;Kim, Wang, Deng, Alvarez, & Li, 2011;Seaton, Caldwell, Sellers, & Jackson, 2008). Gibbons and colleagues (2007), using data from the Family and Community Health Study (FACHS; see Cutrona, Russell, Hessling, Brown, & Murray, 2000), established that the effects of perceived discrimination persisted over time.…”
Section: Mental Health Outcomesmentioning
confidence: 99%
“…This may be more true for those jobs where communication is central to, and may also be influenced by the similarity effect between the job applicant and the decision maker, because accent is often used as a cue for group membership (Kim et al, 2011). Therefore, we aim to examine how accent can influence the recruitment decision making specifically in relation to the IT employers in the NSW region of Australia.…”
Section: Accentmentioning
confidence: 99%